POTENSI 6-AZA-INDAZOLE SEBAGAI TERAPI YANG DAPAT DIPERBAIKI UNTUK PERAWATAN RETINOPATI DIABETIK MELALUI INHIBISI FAKTOR D PENYELESAIAN - Dhitta Shabrina; Ihya Fakrurizal; Afid Brilliana P (Journal Medical Universitas muhammadiyah Makassar, 2019)
Diabetes mellitus is a chronic disease that has a high prevalence in Indonesia. One of diabetes’ complications is Diabetic Retinopathy (DR). DR is one of the highest cause of preventable blindness in the world. The treatment for DR up till then uses intravitreal anti-VEGF injection, intravitreal steroid antiinflammation injection. Intravitreal administration can cause some side effects such as increased intraocular pressure and endophthalmitis. Furthermore, patient’s convenience is also disturbed, for always having to see a medical personnel frequently. One pathogenesis of DR is the activation of the complement system which causes lysis of endothelial cells and results in ischemic damage to the retina. This ischemic effect will stimulate VEGF secretion that manifests in the phase of Proliferative Diabetic Retinopathy (PDR). Inhibitor of D factor, 6-aza indazole is a small size protein, less than 300 Da which has the potential to inhibit progress of DR by interfering with the activation of alternative pathway (AP) of the complement system. This is supported by the in-vivo test result, where there is a significant inhibition of intraocular AP activation continuously for 8 hours after an oral administration of this agent at a dose of 30 mg/kg. But this study is still in a pre-clinical phase that uses mice as the subject. Therefore, there must be a further study and clinical trial to find out the dosage and safety of this agent to be applied to humans. Keywords: 6-aza indazole, alternative pathway, complement factor D inhibitor, diabetic retinopathy